2020
DOI: 10.1177/1074248420924983
|View full text |Cite
|
Sign up to set email alerts
|

Proprotein Convertase Subtilisin/Kexin Type 9 Inhibitors and Ezetimibe on Risk of New-Onset Diabetes: A Systematic Review and Meta-Analysis of Large, Double-Blinded Randomized Controlled Trials

Abstract: Background: Previous meta-analyses have shown that statins may cause incident diabetes. This article reviews randomized controlled trials using proprotein convertase subtilisin/kexin 9 inhibitors (PCSK9i) or ezetimibe on the risk of new-onset diabetes. Methods: Eight trials involving PCSK9i and 3 trials of ezetimibe were selected for review. PubMed, Cochrane Central Register of Controlled Trials, and Clinicaltrials.gov were thoroughly searched for relevant trials. Inclusion criteria included at least 100 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 28 publications
1
5
0
1
Order By: Relevance
“…For positive control outcomes, our findings corroborate previous trials 8 , 11 , 45 , 46 and MR studies 47 , 48 , 49 , 50 that genetically mimicked cardiovascular medications were generally associated with IHD, diabetes, or both as expected.…”
Section: Discussionsupporting
confidence: 89%
“…For positive control outcomes, our findings corroborate previous trials 8 , 11 , 45 , 46 and MR studies 47 , 48 , 49 , 50 that genetically mimicked cardiovascular medications were generally associated with IHD, diabetes, or both as expected.…”
Section: Discussionsupporting
confidence: 89%
“…Neither LDL-C lowering (38.7 mg/dL) nor the use of PCSK9 inhibitors was associated with the incidence of diabetes, respectively, risk ratio = 1.07 (95%CI 1.03-1.11) and risk ratio = 1.00 (95%CI 0.93-1.07) [58]. In line with this evidence, other meta-analyses failed to detect a raised risk of hyperglycaemia or diabetes [59][60][61]. To quantify the safety of PCSK9 inhibitors with a specific focus on type 2 diabetes was also the topic of a Cochrane analysis.…”
Section: Meta-analyses Of Clinical Studiesmentioning
confidence: 80%
“…In this study, a positive diabetes signal was observed only with evolocumab (ROR = 2.5) and not with alirocumab. Although diabetes and worsening glycemic control were not found to be associated with PCSK9 inhibitors in clinical trials ( Carvalho et al, 2017 ; Chiu et al, 2020 ), it has been suggested that the FOURIER trial may not be robust enough to detect diabetes risk ( van Bruggen and Luijendijk, 2019 ). However, in the present study, the lower risk of metabolism and nutrition disorders of PCSK9 inhibitors compared to statins provide reassurance regarding their clinical benefit.…”
Section: Discussionmentioning
confidence: 99%